MODELING AND INFLUENCING FACTOR ANALYSIS OF WORN SPROCKETS IN MINING SCRAPER CONVEYOR - WANG Peng (Jixie qiangdu, 2025)
Sprocket chain ring drive system is the core component of scraper conveyors. The wear of sprocket chain socket is one of the main fault of scraper conveyors. Started with the analysis of the meshing transmission characteristics of the sprocket chain socket, constructed the Archard linear wear model, calculated the wear depth of the chain socket’s linear under working conditions, measured the wear depth of the actual wear sprocket, and verified the accuracy of the Archard linear wear model. The deformation model of ring chain was constructed by finite element method, the shape change of chain socket busbar was predicted, and the shape of sprocket tooth surface after wear was reconstructed according to the change of direction and busbar. The influencing factors of chain socket wear were analyzed. The results show that increasing the hardness of sprocket material, reducing the chain speed, the load and the laying angle can reduce the chain wear. This study provides a basis for the study of the wear pattern of sprocket chain of scraper conveyors.